Laser Powder Bed Fusion and Heat Treatment of an AlCrFe2Ni2 High Entropy Alloy - Vogiatzief, Dimitrios; Evirgen, Alper; Gein, Sergej; Molina, Veronica Rocio; Weisheit, Andreas; Pedersen, Mikkel (Frontiers in Materials, 2020)
Recent research in the Al-Co-Cr-Fe-Ni and Al-Cr-Fe-Ni systems has shown that novel duplex materials composed of FCC and BCC phases can be obtained. Among them, alloys with a composition close to AlCrFe2Ni2 retain their structural properties while being Co-free. Their strength and ductility can be tailored by adjusting the phase fractions of FCC and BCC phases, while the latter is undergoing a spinodal decomposition into ordered and disordered BCC phases. Further improvement of the properties is expected with the use of novel processing techniques such as laser powder bed fusion. This process stands out due to high geometric complexity capabilities, a wide range of accessible processing parameters, and high cooling rates that support microstructure refinement. Within the frame of the present study, alloy powder around the composition AlCrFe2Ni2 was produced and coupons for material characterization were built with laser powder bed fusion. In this paper, the following will be presented: i) prealloyed powder properties, ii) laser powder bed fusion processing of the material, iii) heat treatments and their subsequent effect on microstructure, and iv) mechanical properties obtained by three-point bending and microhardness tests. A highlight of this study is the novel pathway to obtain an ultrafine duplex microstructure, which forms upon heat treatment from a metastable as-built microstructure. A spinodally decomposed BCC microstructure, retained due to solidification under high cooling rates, is used to nucleate and grow FCC micro-platelets during a subsequent heat treatment step. This ultrafine duplex material cannot be obtained under conventional processing; thus, it can be considered a unique additive manufacturing material. In the context of the heat treatment study carried out in the present work, the influence of heat treatment parameters on the phase fraction of FCC platelets and the resulting hardness and flexural properties will be discussed. Finally, the current challenges concerning the processing of the alloy and the possible optimization paths for best material performance will be discussed.